Meningkatkan Hasil Belajar dengan Menggunakan Media Kartu Cerita untuk Menemukan Ide Pokok Paragraf pada Pelajaran Bahasa Indonesia Kelas 4 - Brawijaya; Hamidah Noer; Ervina Eka Subekti (Pascasarjana Universitas PGRI Semarang, 2025)
Based on learning activities using Story Card Media, it has provided opportunities for students to explore their individual abilities through the worksheets provided. Using Story Card Media makes children confident in their answers and opinions. Students begin to have the courage to ask and answer questions about things they don't understand, and then this increases. The use of Story Card Media has a good impact on learning Indonesian with the material of finding the Main Idea of ​​a Paragraph.